The Role of Arabic in Strengthening Muslim Religious Identity: Insights from Minangkabau’s Social Transformation - Naska, Isral (Islam Transformatif : Journal of Islamic Studies, 2024)
This study aims to analyze the role of Arabic as a foreign language in strengthening the religious identity of Muslims as a social group. Previous studies indicate that religious identity can shift due to various factors, with religious understanding being the most influential. From the Islamic perspective, the Qur'an, regarded as the holy scripture and written in Arabic, serves as the primary source of Islamic teachings. Thus, proficiency in Arabic is considered a crucial factor in shaping Islamic identity. However, previous research has not thoroughly examined how Arabic strengthens Muslim religious identity from a sociological viewpoint. This study employs a qualitative method through literature review, focusing on Minangkabau's history as a case of socio-cultural acceptance of Islam. The analysis is conducted using William H. Sewell Jr.'s theory of social transformation. The findings reveal that Arabic plays a central role as a resource in Minangkabau's social transformation, particularly in the formation and reinforcement of Muslim religious identity at the social level.